2016
DOI: 10.1080/13880209.2016.1199040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an ethanol extract and the diterpene, xylopic acid, of Xylopia aethiopica fruits in murine models of musculoskeletal pain

Abstract: Context: Fruits of Xylopia aethiopica (Dunal) A. Rich. (Annonaceae) are used traditionally to manage arthritis, headache and other pain disorders. Objective: The analgesic properties of the X. aethiopica ethanol fruit extract (XAE) and xylopic acid (XA) were evaluated in musculoskeletal pain models. Materials and methods: Acute muscle pain was induced in gastrocnemius muscle of Sprague-Dawley rats with 3% carrageenan (i.m.). Rats received XAE (30-300 mg/kg), XA (10-100 mg/kg) or morphine (1-10 mg/ kg) after 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Although the XA monotherapy experiment did not significantly prevent weight loss, the combination therapy with ART and AQ showed significant reduction in weight loss in the 10.6 mg/kg and 12.1 mg/kg combination doses. This observation correlates with other studies where a combination of xylopic acid and cryptolepine prevented a loss in body weight in mice infected with P. berghei ANKA (12,16).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the XA monotherapy experiment did not significantly prevent weight loss, the combination therapy with ART and AQ showed significant reduction in weight loss in the 10.6 mg/kg and 12.1 mg/kg combination doses. This observation correlates with other studies where a combination of xylopic acid and cryptolepine prevented a loss in body weight in mice infected with P. berghei ANKA (12,16).…”
Section: Discussionsupporting
confidence: 91%
“…Xylopic acid was extracted from Xylopia aethiopica as previously described (14)(15)(16). Fresh unripe fruits of Xylopia aethiopica purchased from the Ho Central Market in Ghana were shadedried and pulverized with a hammer mill.…”
Section: Xylopic Acid Extractionmentioning
confidence: 99%
“…Xylopic acid crystals formed after the concentrate had been allowed to stand for 72 h. This was washed with petroleum ether at 40–60 °C repeatedly to remove all unwanted materials. The resulting crude xylopic acid was finally purified in 96% ethanol by recrystallization as previously described [ 12 , 13 , 17 ]. The purity of xylopic acid (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the major phytochemical constituent in the fruits and seeds is kaurene diterpenoid, xylopic acid (Figure ; Biney et al, ). Some authors have attributed the effects of the crude extract to this acid component with comparative studies, corroborating this hypothesis (Woode et al, ; Woode, Ameyaw, Boakye‐Gyasi, & Abotsi, ). In other pharmacological studies, the ethanolic fruit extract has been shown to reduce signs of inflammation in adjuvant‐induced arthritis and lipopolysaccharide‐induced systemic anaphylaxis (Obiri & Osafo, ; Obiri, Osafo, Oppong‐Sarfo, & Prah, ).…”
Section: Introductionmentioning
confidence: 67%